If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(y + 2) = -6y Reorder the terms: -5(2 + y) = -6y (2 * -5 + y * -5) = -6y (-10 + -5y) = -6y Solving -10 + -5y = -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. -10 + -5y + 6y = -6y + 6y Combine like terms: -5y + 6y = 1y -10 + 1y = -6y + 6y Combine like terms: -6y + 6y = 0 -10 + 1y = 0 Add '10' to each side of the equation. -10 + 10 + 1y = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 1y = 0 + 10 1y = 0 + 10 Combine like terms: 0 + 10 = 10 1y = 10 Divide each side by '1'. y = 10 Simplifying y = 10
| 12+4x+6=6+4x | | 0.2a-1.42=0.6-1.3-(2a-3) | | -18-4x=-3(-x+2)-4x | | 9=m-23/7 | | 285=13p+180 | | 7z+1-2z=8+4z-4 | | 5x^2-21=-22 | | 4x+4+3x-12=x+40 | | t=13p+285 | | 2-2(-5n-10)=30 | | -12(x+y)=-12(240) | | -4x-3=-x-3 | | 8(5x+12)=576 | | 4x+5+3x-12=x+40 | | 31=6-(x+4) | | 2b+7(b+5b)=220 | | 6(3k+1)-30=3(2k-4) | | 5z-6=8z-4z | | 9(6x+5)=423 | | t=13p+180 | | -2/3×18=-12 | | 30+1.50=12+3x | | -2/3×18= | | 9+3v=2-v-3v | | 42=-3(y+8) | | -x-10.5=6x+31.5 | | -0.0002x^2-0.008x+0.05=0 | | 3n+6=99 | | X+y(11)=156 | | log(36)+log(x)=log(5)-log(x) | | -(j-26)+42=68 | | -0.0002x-0.008x+0.05=0 |